2011
DOI: 10.48550/arxiv.1109.0396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The $KD$, $ηD_s$ interaction in finite volume and the nature of the $D_{s^* 0}(2317)$ resonance

A. Martínez Torres,
L. R. Dai,
C. Koren
et al.

Abstract: An SU(4) extrapolation of the chiral unitary theory in coupled channels done to study the scalar mesons in the charm sector is extended to produce results in finite volume. The theory in the infinite volume produces dynamically the D s * 0 (2317) resonance by means of the coupled channels KD, ηD s . Energy levels in the finite box are evaluated and, assuming that they would correspond to lattice results, the inverse problem of determining the bound states and phase shifts in the infinite volume from the lattic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 35 publications
(83 reference statements)
2
41
0
Order By: Relevance
“…Recently, the problem of extracting continuum quantities from synthetic lattice data has also been also discussed in Ref. [31] in the context of meson-meson interaction with charm and the D s * 0 (2317) resonance. The extraction of continuum quantities, at higher energies, may also be performed using dynamical coupled-channels approaches as shown in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the problem of extracting continuum quantities from synthetic lattice data has also been also discussed in Ref. [31] in the context of meson-meson interaction with charm and the D s * 0 (2317) resonance. The extraction of continuum quantities, at higher energies, may also be performed using dynamical coupled-channels approaches as shown in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This pole is interpreted as the DK bound state, D * s0 (2317) which has been supported by both lattice QCD [35][36][37][38][39][40][41][42][43] and phenomenological studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Based on the DD interaction potential, Eq.…”
Section: Results and Discussion A 2-body Partmentioning
confidence: 86%
“…The discovery of the D * s0 (2317) [1][2][3] and subsequent phenomenological studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17] imply that there is a strongly attractive interaction between D and K. The prevailing idea that the D * s0 (2317) can be understood as a molecular state has been confirmed by many Weinberg-Tomozawa potential calculations [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and lattice QCD simulations [35][36][37][38][39][40][41][42][43]. It is also found that there is a long-range attractive potential between D and D * s0 (2317).…”
mentioning
confidence: 99%
“…MeV respectively [14], thus D * s0 (2317) is difficult to be interpreted as a conventional cs meson. On the other hand, due to the strongly attractive DK interaction predicted by chiral perturbation theory and lattice QCD [15,16], D * s0 (2317) can be easily explained as a DK molecule [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The same molecular picture is adopted to study the pentaquark states, i.e., P c (4312), P c (4440), and P c (4457), discovered by the LHCb Collaboration [34].…”
Section: Introductionmentioning
confidence: 99%